Synthesis and antimicrobial activity of 4′,5,7-trihydroxy-3′- prenylflavanone - Mohamed Adib, Adiana; Ahmad, Farediah; Idris, Muhammad Sum (Indian Academy of Sciences, 2008)
4′,5,7-Trihydroxy-3′-prenylflavanone was synthesized and tested for antibacterial effects against Bacillus subtilis, Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The synthesized compounds were characterized using UV, IR, MS and 1H and 13C NMR data. The antibacterial screening of the synthesized compounds were performed in vitro by the filter paper disc diffusion method.